Copper-catalyzed oxidative multicomponent reaction: synthesis of imidazo fused heterocycles with molecular oxygen. Issue 39 (9th August 2018) - Li, Xianwei; Wang, Tianzhang; Lu, Yu-Jing; Ji, Shaomin; Huo, Yanping; Liu, Bifu
Abstract : An oxidative cascade that involves multicomponent reaction comprising a terminal alkyne, 2-amino N-heterocycle, benzyl or allylic bromide with molecular oxygen, delivering densely functionalized imidazo fused heterocycles, is achieved. Abstract : An oxidative cascade that involves multicomponent reaction comprising a terminal alkyne, 2-amino N-heterocycle, benzyl or allylic bromide with molecular oxygen, delivering densely functionalized imidazo fused heterocycles, is described. This reaction features a cheap catalyst, a green oxidant, and readily available starting materials, which make the overall synthesis applicable in the quick access to relevant pharmaceutical molecules with imidazole derived heterocycles.